1995
DOI: 10.1007/bf00860734
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory blood pressure monitoring in paediatric patients treated by regular haemodialysis and peritoneal dialysis

Abstract: Ambulatory blood pressure monitoring (ABPM) has been shown to be more representative of blood pressure (BP) levels than casual BP measurements in adult patients treated by haemodialysis (HD). In this study we compared ABPM using the oscillometric SpaceLabs 90207 monitor with casual BP measurements in 35 paediatric patients [17 treated by peritoneal dialysis (PD) and 18 by HD]. Heart rate and plasma concentrations of atrial natriuretic peptide were also measured. No correlations were found between ABPM and caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 21 publications
3
39
0
2
Order By: Relevance
“…In a study of 18 pediatric hemodialysis patients, no correlation was found between ambulatory and predialysis BP measurements (22). In five patients, BP assessed by predialysis recordings was overestimated, and in three it was underestimated compared with ambulatory measurements (22). In a study of 12 pediatric hemodialysis patients, a modest correlation of approximately 0.5 was found between casual and am- bulatory BP measurements for both systolic and diastolic BP (23).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In a study of 18 pediatric hemodialysis patients, no correlation was found between ambulatory and predialysis BP measurements (22). In five patients, BP assessed by predialysis recordings was overestimated, and in three it was underestimated compared with ambulatory measurements (22). In a study of 12 pediatric hemodialysis patients, a modest correlation of approximately 0.5 was found between casual and am- bulatory BP measurements for both systolic and diastolic BP (23).…”
Section: Discussionmentioning
confidence: 92%
“…Data on ambulatory BP monitoring in pediatric hemodialysis patients are limited. In a study of 18 pediatric hemodialysis patients, no correlation was found between ambulatory and predialysis BP measurements (22). In five patients, BP assessed by predialysis recordings was overestimated, and in three it was underestimated compared with ambulatory measurements (22).…”
Section: Discussionmentioning
confidence: 93%
“…In most of the comparative studies for BP control, it was reported that hypertension is better controlled by haemodialysis than CAPD. 6,8,16 However, Rodby et al 9 reported haemodialysis is associated with higher systolic blood pressures than peritoneal dialysis. The differences in the results of the studies are probably due to the differences in volume status of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…ABPM allows a better assessment in the course of BP levels during the day. 5,6 It was also reported that abnormal BP rhythm, which is common in patients with endstage renal failure, might be associated with target organ damage resulting from hypertension in women. 7 Numerous studies with 24-h ABPM have been reported in haemodialysis and CAPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…A single 'office' BP may underestimate the true prevalence of hypertension, and ambulatory BP monitoring is increasingly used to diagnose and manage hypertension in dialysis patients [88][89][90].…”
Section: Fluid Overload and Hypertensionmentioning
confidence: 99%